A systematic review on the genetic analysis of paragangliomas: primarily focused on head and neck paragangliomas - Guha, A; Musil, Z; Vicha, A; Zelinka, T; Pacak, K; Astl, J; Chovanec, M (Neoplasma, 2019)
Head and neck paragangliomas Paragangliomas and pheochromocytomas are rare, mostly benign neuroendocrine tumors, which are embryologically derived from neural crest cells of the autonomic nervous system. Paragangliomas are essentially the extra-adrenal counterparts of pheochromocytomas. As such this family of tumors can be subdivided into head and neck paragangliomas, pheochromocytomas and thoracic and abdominal extra-adrenal paragangliomas. Ten out of fifteen genes that contribute to the development of paragangliomas are more susceptible to the development of head and neck paragangliomas when mutated. Gene expression profiling revealed that pheochromocytomas and paragangliomas can be classified into two main clusters (C1 and C2) based on transcriptomes. These groups were defined according to their mutational status and as such strongly associated with specific tumorigenic pathways. The influence of the main genetic drivers on the somatic molecular phenotype was shown by DNA methylation and miRNA profiling. Certain subunits of succinate dehydrogenase (SDHx), von Hippel-Lindau (VHL) and transmembrane protein 127 (TMEM127) still have the highest impact on development of head and neck paragangliomas. The link between RAS proteins and the formation of pheochromocytoma and paragangliomas is clear due to the effect of receptor tyrosine-protein kinase (RET) and neurofibromatosis type 1 (NF1) in RAS signaling and recent discovery of the role of HRAS. The functions of MYC-associated factor X (MAX) and prolyl hydroxylase 2 (PHD2) mutations in the contribution to the pathogenesis of paragangliomas still remain unclear. Ongoing studies give us insight into the incidence of germline and somatic mutations, thus offering guidelines to early detection. Furthermore, these also show the risk of mistakenly assuming sporadic cases in the absence of definitive family history in head and neck paragangliomas.
Keywords: mutace; Mutation; lidé; paragangliom; Head and Neck Neoplasms; Humans; Paraganglioma; nádory hlavy a krku